2015
DOI: 10.1016/j.virol.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between the Hepatitis C proteins NS4B and NS5A is involved in viral replication

Abstract: Hepatitis C virus (HCV) replicates in membrane associated, highly ordered replication complexes (RCs). These complexes include viral and host proteins necessary for viral RNA genome replication. The interaction network among viral and host proteins underlying the formation of these RCs is yet to be thoroughly characterized. Here, we investigated the association between NS4B and NS5A, two critical RC components. We characterized the interaction between these proteins using fluorescence resonance energy transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Tryptophan residues in several proteins play important role in protein–protein interactions . At the binding interface of the protein–protein interaction, the probability of having tryptophan residues is maximal compared to other amino acids .…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan residues in several proteins play important role in protein–protein interactions . At the binding interface of the protein–protein interaction, the probability of having tryptophan residues is maximal compared to other amino acids .…”
Section: Discussionmentioning
confidence: 99%
“…The locations of the input mutation and the rescue reversion in the present study were striking. Unlike the previous two studies, where the input mutation resides on helix 1 of the C-terminal domain of NS4B and the rescue reversion or site of interaction resides on domain I of NS5A (52,53), in the present study, the input mutation resides at the NS5A N-terminal anchor helix region, and the rescue reversion resides on helix 2 of the C-terminal domain of NS4B. Considering that NS4B interacts directly with NS5A during replication, if the findings of the present study are combined with the findings of others (40,52,53), and if one assumes that the genetic interactions observed by these efforts represent physical contact surfaces, the arrangement of the input mutation and the rescue reversion suggests that the interaction between NS5A and NS4B occurs at multiple sites in a parallel head-to-tail orientation on the surface of the ER.…”
Section: Figmentioning
confidence: 82%
“…So far, several studies demonstrated the interaction between NS4B and NS5A but with limited information about the nature of the interaction. A recent study showed that the interaction between domain I of NS5A and helix 1 of the C-terminal domain of NS4B is involved in HCV RNA replication (52). In another study, revertant analysis showed that the effect of mutations in helix 1 of the C-terminal domain of NS4B is rescued by an intergenic reversion situated around the center of domain I of NS5A (53).…”
Section: Figmentioning
confidence: 99%
“…NS4B also forms oligomeric complexes via self-interaction, which is required for HCV RNA replication, in addition to the above-mentioned RO formation [ 30 , 37 , 38 ]. The interaction between the NS4B and NS5A is reportedly involved in viral replication [ 129 , 130 ].…”
Section: Genome Replicationmentioning
confidence: 99%